Analisis Hubungan Toke dan Petani Sawit Pola Swadaya di Desa Pangkatan Kecamatan Pangkatan Kabupaten Labuhan Batu Provinsi Sumatera Utara - Nuhida Wati Sitohang; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aimed to determine the characteristics of tauke and farmers conducted in Pangkatan Village Subdistrict Pangkatan District Labuhan Batu North Sumatera Province, analyzed the relationship of tauke conducted in Pangkatan Village Subdistrict Pangkatan District Labuhan Batu North Sumatera Province. This study was conducted in Pangkatan Village Subdistrict Pangkatan District Labuhan Batu, North Sumatera Province. The sampling method used Random Sampling. The data analysis used were descriptive analysis with the presentation of qualitative analysis. the relationship form that connected between farmers and ‘tauke’ were marketing of palms oil. The farmers relied to ‘tauke’ to sell their palms oil. The marketing of palms oil were not balanced, where ‘tauke’ were more advantaged than the farmers. The factors caused the relationship of ‘tauke’ and farmers included palms oil marketing, costs of farming, costs of consumption, costs of health, and costs of children education.while, factors of the relationship between ‘tauke’ and farmers were capital factors (economic), production factors, and family factors. Keyword: Marketing, patron-client, Farmers, tauke and Rumbber’